Diagnostic value of abdominal CT scan in ovarian tumors in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January 2017 to December 2018 - Ida Bagus Gede Ramayuda; Lies Mardiyana; Dyah Erawati; Indra Yuliati (Universitas Airlangga, 2021)
HIGHLIGHTS1. Ovarian tumors diagnostic value has been determined using the tools on contrast-enhanced abdominal CT Scan.2. The tools including primary finding like mass size, septation, solid component, and additional finding such as ascites, peritoneal implants, lymph node enlargement.3. Most tumors were ovarian malignant tumors according to their histopathological results.4. Contrast-enhanced abdominal CT Scan of ovarian tumors evaluated by the tools gave better and more reliable diagnostic value than without using the tools.ABSTRACTObjectives: The purpose of this study was to determine the diagnostic value of contrast-enhanced abdominal CT scan in ovarian tumors in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, to provide scientific and clinical benefits.Materials and Methods: Samples were taken retrospectively by contrast-enhanced abdominal CT scan raw data in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January 2017 to December 2018. Using inclusion and exclusion criteria, a total of 88 samples were obtained and reviewed blindly by Female Organ Division of Radiology Department, Faculty of Medicine Universitas Airlangga, and by using